2019
DOI: 10.5194/acp-2019-738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Open cells can decrease the mixing of free-tropospheric biomass burning aerosol into the south-east Atlantic boundary layer

Abstract: This work presents synergistic satellite, airborne and surface based observations of a Pocket of Open Cells (POC) in the remote south-east Atlantic. The observations were obtained over and upwind of Ascension Island during the CLouds and Aerosol Radiative Impacts and Forcing (CLARIFY) and the Layered Smoke Interacting with Clouds (LASIC) field experiments. A novel aspect of this case-study is that an extensive free-tropospheric biomass burning aerosol plume that had been transported from the African continent … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…The SSA assumption not only has a large impact on the scattering AOT, it also influences, to a lesser extent, the AAOT. Peers et al (2019) also showed that the AAOT is sensitive to the assumed asymmetry factor. The asymmetry factor assumption for the MOD06ACAERO retrieval is AOT dependent (with the asymmetry factor taking values of 0.60 and 0.62 at a 30 wavelength of 0.55 µm for AOT value of 0.5 and 1.5, respectively) and is smaller than the asymmetry factor assumed for the SEVIRI algorithm (i.e.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…The SSA assumption not only has a large impact on the scattering AOT, it also influences, to a lesser extent, the AAOT. Peers et al (2019) also showed that the AAOT is sensitive to the assumed asymmetry factor. The asymmetry factor assumption for the MOD06ACAERO retrieval is AOT dependent (with the asymmetry factor taking values of 0.60 and 0.62 at a 30 wavelength of 0.55 µm for AOT value of 0.5 and 1.5, respectively) and is smaller than the asymmetry factor assumed for the SEVIRI algorithm (i.e.…”
mentioning
confidence: 92%
“…The South East Atlantic Ocean (SEAO) is an ideal region to analyse the effects of 5 partially absorbing aerosols on the radiative budget, the atmospheric stability, clouds and precipitation. The biomass burning aerosols emitted from July to October in southern Africa are mostly transported westward in the residual continental boundary layer in the free troposphere (Abel et al, 2019). These absorbing biomass burning particles are frequently observed above the extensive stratocumulus deck covering the SEAO.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations